Phase diagram and superconductive properties of splat-cooled CuxLa1-x - Favaron, J. (1980)
Fil: Favaron, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina